Sitagliptin protects proliferation of neural progenitor cells in diabetic mice - Bachor, Tomás Pedro (2015)
Sitagliptin (SIT) is a dipeptidyl peptidase-4 (DPP-4) inhibitor that enhances the effects of incretin hormones, such as Glucose-dependent Insulinotropic Peptide (also known as Gastric Inhibitory Polypeptide, GIP) and Glucagon-Like Peptide 1 (GLP-1). We have now evaluated the effect of SIT on proliferation of neural progenitors in diabetic mice. A condition resembling the non-obese type 2 diabetes mellitus (D2) was achieved by a combination of streptozotocin and nicotinamide (NA-STZ), whereas a type 1-like disease (D1) was provoked by STZ without NA. Nondiabetic mice received vehicle injections. Cell proliferation was estimated by bromodeoxyuridine (BrdU) incorporation in two different regions of the subventricular zone (SVZ), the largest reserve of neural stem cells in the adult brain. SIT treatment did not modify the high fasting blood glucose (BG) levels and intraperitoneal glucose tolerance test (IPGTT) of D1 mice. By contrast, in D2 mice, SIT treatment significantly reduced BG and IPGTT. Both D1 and D2 mice showed a substantial reduction of BrdU labeling in the SVZ. Remarkably, SIT treatment improved BrdU labeling in both conditions. Our findings suggest that SIT would protect proliferation of neural progenitor cells even in the presence of non-controlled diabetic alterations.